EVALUASI PELAKSANAAN BINA IMAN SPIRITUALITAS FRANSISKAN TERHADAP PENINGKATAN KEIMANAN PADA GURU SEKOLAH DASAR MARSUDIRINI SEMARANG - Fransisca Romana Wuriningsih (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2020)
Marsudirini Elementary School teachers have received faith coaching in the form of trainings, retreats, recollections, inspires, on a regular basis by the Foundation. In the course of time, some of the Masters have not shown maximum service to love in their work. The purpose of this study was to describe teacher perceptions and their impact on the implementation of teacher training and implementation in carrying out love service tasks in the field. The scope taken; Marsudirini Elementary School, Jl. Youth 159-Semarang. The sample is 20 teachers. The focus of the research is on the implementation, impact of training, and implementation of compassionate service in the field. How to collect data is done with a questionnaire. The data was processed using descriptive analysis. The results of the research based on the questionnaire showed the number of 4.0 or 80% on the perception variable of the Marsudirini Elementary School Teacher in the Implementation of the Franciscan Faith Development. This means that the Marsudirini Elementary School teacher responded positively to the activities of the Franciscan Faith Development. Next, the second variable regarding the Impact of Following the Franciscan Faith Development in the Marsudirini Scope shows a figure of 4.3 or 86%, this means that after the implementation of the Franciscan Faith Development activities there is a very good impact for the Marsudirini Elementary School teachers. The third variable regarding the Implementation of the Franciscan Faith Development in Daily Life shows the number 4.5 or 90%, this means that the Franciscan Faith Development activities can help Marsudirini Elementary School teachers in realizing their faith in their daily lives very well. Based on the results of the research, it is recommended that: Coaching is continued regularly and reflection is held periodically in each activity.